1988
DOI: 10.1002/j.1460-2075.1988.tb02903.x
|View full text |Cite
|
Sign up to set email alerts
|

A carboxyl-terminal cysteine residue is required for palmitic acid binding and biological activity of the ras-related yeast YPT1 protein.

Abstract: The Saccharomyces cerevisiae YPT1 gene codes for a ras‐like, guanine nucleotide‐binding protein which is essential for cell viability. The functional significance of two consecutive cysteines at the very carboxyl‐terminal end of this protein and in ypt homologues of other eukaryotic species was examined. YPT1 gene mutations were generated that either led to substitutions by serine or the deletion of one or both C‐terminal cysteines. The consequences of the mutations were checked in cells after replacing the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
1

Year Published

1989
1989
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 28 publications
3
61
1
Order By: Relevance
“…The correct C-terminal sequence is essential for processing and membrane insertion of p2lras, which is cleaved, carboxymethylated, isoprenylated, and palmitoylated (9). The two consecutive Cys residues of rabi (YPT1) are also essential for acylation and membrane association (14). The observation that p25rab3A is partially cytosolic, like YPT1 (14), therefore supports the idea that the different c-terminal consensus sequences comprise signals for different types of processing and localization.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The correct C-terminal sequence is essential for processing and membrane insertion of p2lras, which is cleaved, carboxymethylated, isoprenylated, and palmitoylated (9). The two consecutive Cys residues of rabi (YPT1) are also essential for acylation and membrane association (14). The observation that p25rab3A is partially cytosolic, like YPT1 (14), therefore supports the idea that the different c-terminal consensus sequences comprise signals for different types of processing and localization.…”
Section: Resultsmentioning
confidence: 73%
“…These levels of contamination cannot account for the levels of p25rab3A detected in the membrane fractions (116% of cytosolic p25rab3A in the detergent-solubilized particulate fraction; 30% in the purified membranes). The rab3A gene product, like YPT1 (rabl) (14), therefore appears to be partially membrane bound and partially cytosolic. DISCUSSION We have prepared an antipeptide antiserum that specifically detects the GTP-binding protein p25rab3A and have shown that this protein is expressed exclusively in brain tissue of the tissues tested.…”
Section: Resultsmentioning
confidence: 99%
“…Ras-related proteins are involved in regulating a wide range of cellular processes, including cell proliferation, differentiation, intracellular trafficking (7, 24), membrane ruffling, and assembly of actin stress fibers (43,44). Although these proteins serve very diverse functions, their ability to associate with cell membranes is a fundamental requirement for biological activity (review in reference 20) such that mutations in Ras, Rho, and Rab proteins which block membrane localization also render these proteins biologically inactive (2,21,40,49,51).The mechanism of attachment of Ras proteins to the inner surface of the plasma membrane provides a model for the membrane targeting of other Ras-related proteins. The C terminus of Ras terminates in a CAAX motif (C = cysteine, A = aliphatic amino acid, X = any amino acid) which undergoes farnesylation of the cysteine residue (12, 28), proteolysis by an endopeptidase to remove the AAX amino acids (19, 23), and carboxyl-methyl esterification of the cysteine (16,23 (510) 222 9758. signal is a polylysine domain in K-Ras and cysteine palmitoylation sites in the H-and N-Ras proteins.…”
mentioning
confidence: 99%
“…Ras-related proteins are involved in regulating a wide range of cellular processes, including cell proliferation, differentiation, intracellular trafficking (7, 24), membrane ruffling, and assembly of actin stress fibers (43,44). Although these proteins serve very diverse functions, their ability to associate with cell membranes is a fundamental requirement for biological activity (review in reference 20) such that mutations in Ras, Rho, and Rab proteins which block membrane localization also render these proteins biologically inactive (2,21,40,49,51).…”
mentioning
confidence: 99%
“…Less is known about the posttranslational processing of proteins in the second and third groups. A member of the second group of proteins, the yeast YPT1 protein, has been reported to be palmitoylated on one or both of the cysteine residues at the C-terminal region, but this result has not been substantiated (11). In the case of the small G proteins in the third group, no information concerning their posttranslational modification is available.…”
mentioning
confidence: 99%